EEG-correlates of trait anxiety in the stop-signal paradigm - Savostyanov, Alexander N.; Tsai, Arthur C.; Liou, Michelle; Levin, Evgeny A.; Lee, Juin-Der; Yurganov, Alexey V.; Knyazev, Gennady G. (Neuroscience letters, 2009)
The relationship between trait anxiety and event-related EEG oscillatory reactions in the stop-signal paradigm was studied in 15 non-clinical subjects with average age of 26 years (13 men). In the paradigm, subjects responded to target stimuli by pressing one of the two choice buttons. In 30 out of 130 trials, target presentation was followed by a stop-signal, indicating that subjects had to refrain from a prepared motor response. The subject's level of anxiety was assessed using the State Trait Anxiety Inventory. Wide-band desynchronization (8–25 Hz) was found before button-press. It was sustained after the subjects pressed the button at 7–14 Hz frequency range. Also, synchronization at 15–25 Hz band occurred in 400–1400 ms after the button-press. Synchronization at lower frequencies (1–7 Hz) was also found during 0–700 ms after the stop-signal onset. Also, desynchronization at 8–20 Hz was found in 300–800 ms after stop-signal onset. The group with higher anxiety showed desynchronization at 10–13 Hz in 0–800 ms after the button-press, whereas the group with lower anxiety showed synchronization at the same frequency range. In 0–600 ms after stop-signal onset, desynchronization at 8–13 Hz was observed in the group with higher anxiety, whereas the group with lower anxiety demonstrated synchronization or weak desynchronization. Our findings support the Eysenck et al. [M.W. Eysenck, N. Derakshan, R. Santos, M.G. Calvo, Anxiety and cognitive performance: attentional control theory, Emotion 7(2) (2007) 336–356] theory that subjects with higher anxiety have more attentional control over reaction and increased use of processing resources as compared with lower anxiety subjects.